2005
DOI: 10.1080/17425960500288390
|View full text |Cite
|
Sign up to set email alerts
|

The Initial Education of High School Teachers: A critical review of major issues and trends

Abstract: This paper draws on major research findings in international literature in order to provide a critical review of a number of key issues and trends in the initial education of high school teachers. Firstly, this paper contextualizes the prevalent discourse surrounding the field of initial teacher education (ITE) and explores the effect that this discourse has on the conceptualization of teachers' work. Secondly, this paper focuses on the debates regarding the most propitious site for the teacher education enter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
0
9
0
4
Order By: Relevance
“…Yet both student teachers by the end of their course had made subtle shifts and changes to their thinking through a critical engagement with and challenge to their own beliefs and values. This perhaps reflects a movement away from what Sultana (2005) suggests is the traditional academic model of teacher as professional where assimilation and socialization into the existing models in schools may hold sway. Instead this chimes with teacher as a critical agent for change through formal or informal research into practice (Sachs, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Yet both student teachers by the end of their course had made subtle shifts and changes to their thinking through a critical engagement with and challenge to their own beliefs and values. This perhaps reflects a movement away from what Sultana (2005) suggests is the traditional academic model of teacher as professional where assimilation and socialization into the existing models in schools may hold sway. Instead this chimes with teacher as a critical agent for change through formal or informal research into practice (Sachs, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Sultana (2005), citing McDiarmid et al (1989), indicated that the application of student-centred teaching methods depends on the depth and breadth of teachers' subject matter knowledge. When teachers lack depth and breadth in their subject matter knowledge, they emphasize direct instruction methods so as to J Educ Change (2008) 9:281-304 293 minimize the risk of falling into unknown or doubtful areas.…”
Section: Imbalance Of the Knowledge Bases Of Teacher Education For Sementioning
confidence: 97%
“…Others contend that pedagogical preparation not only enhances the performance of students but also contributes to retaining teachers in the teaching profession (Darling-Hammond 2000b). Many writers in teacher education agree that teacher preparation should include subject matter, professional courses, and adequate field experiences (Buchberger 2000;Shulman 1987;Sultana 2005). Wilson et al (2002) reviewed studies that assessed the effect of the various components of teacher education on students' learning.…”
Section: Curriculum In Ethiopian Teacher Education Programs: Marginalmentioning
confidence: 98%
See 1 more Smart Citation
“…It functions in support of a neo-liberal economic agenda (Sultana, 2005;Apple, 2001;Smyth, 2006;Hartley, 1997) and appropriates the technicist language typically used in the business sector. The following example, from Australia, quite vividly demonstrates this issue:…”
Section: Discourse Of the New Managerialism/performativitymentioning
confidence: 99%